Significant fibrosis assessed by liver biopsy among Chinese bariatric surgery patients: A prospective cross-sectional study - Huang, Yongsheng; Dong, Shiliang; Wang, Cunchuan; Dong, Zhiyong; Chen, Wenhui (Frontiers in Endocrinology, 2023)
Background: Fibrosis stages affects the clinical prognoses of non-alcoholic fatty liver disease (NAFLD). However, scarce data exists about the prevalence and clinical features of significant fibrosis in Chinese bariatric patients. This study was aimed to investigate the prevalence and identify the predictors of significant fibrosis in bariatric patients. Methods: We prospectively enrolled the patients performing intra-operative liver biopsies during bariatric surgery from a bariatric surgery center in a university hospital between May 2020 and January 2022. Anthropometric characteristics, co-morbidities, laboratory data and pathology reports were collected and analyzed. The performance of non‐invasive models was evaluated. Results: Of 373patients, 68.9%% had non-alcoholic steatohepatitis (NASH) and 60.9% exhibited fibrosis. Significant fibrosis was present in 9.1% of patients, advanced fibrosis in 4.0%, and cirrhosis in 1.6%. Multivariate logistic regression showed that, increasing age (odds ratio [OR], 1.06; p=0.003), presence of diabetes (OR, 2.62; p=0.019), elevated c- peptide (OR, 1.26; p=0.025) and elevated aspartate aminotransferase (AST) (OR, 1.02; p=0.004) were independent predictors of significant fibrosis. The non-invasive models, AST to Platelet ratio (APRI), Fibrosis‐4 (FIB-4) and Hepamet fibrosis scores (HFS) provided greater accuracy for predicting significant fibrosis, compared to the NAFLD Fibrosis Score (NFS) and BARD score. Conclusion: More than two thirds of bariatric surgery patients had NASH and the prevalence of significant fibrosis was high. Elevated levels of AST and c- peptide, advanced age and diabetes indicated higher risk of significant fibrosis. Non-invasive models, APRI, FIB-4 and HFS can be used to identify significant liver fibrosis in bariatric surgery patients.